La cabaña del Tío Tom (Uncle Tom’s Cabin), la esclavitud atlántica y la racialización de la esfera pública en la ciudad de México de mediados del siglo XIX - Castilho, Celso Thomas (El Colegio de México, A.C., 2019)
The 1857 theatrical productions of Uncle Tom’s Cabin in Mexico City must be understood as part of the cultural phenomenon of “Tom Mania” that swept the Atlantic world in the 1850s. Nevertheless, both historians and literary critics have ignored the impact of Harriet Beecher Stowe’s famous novel in Mexico, as well as its importance in Latin America as a whole. One consequence of this has been a lack of attention paid to how the Spanish imperial project, which included slavery, influenced the development of a Hispano-Mexican intellectual field regarding issues such as slavery, race and abolitionism. This article sheds light on these connections through a transnational perspective on the circulation of Uncle Tom’s Cabin in Mexico City. The first part traces how it and other important contemporary texts that dealt with the issue of slavery –Victor Hugo’s Bug-Jargal and Gustave de Beaumont’s Marie, or Slavery in the United States– conquered the bookstores, periodicals and literary salons of the capital. The second part focuses on the 1857 theatrical productions of the novel, arguing that aspects of these productions underscored the apparent acceptance and familiarity with minstrel tropes in the cultural arena, showing how these anti-slavery plays nevertheless reinforced practices that stigmatized blackness.